Program Kerja Unggulan Pengembangan UMKM Usaha Kuliner dan Fashion di Desa Wanaraja - Aisyah, Risa; Kalimat, Arul Budi; Maulana, Ilham Ahmad; Harlini, Meti; Uyun, Syifa Qurrotul; Destia, Triyanda Putra; Aziz, Rafi Nurkholiq; Ilyasa, Salya; Nuraisah, Siti; Adela, Yoga; Gunawan, Sendi Febrian; Fadilah, Luthfi Aqshol; Setiawan, Muhamad Yogi; Muntiani, Via; Febis, Delsa Tria; Padini, Dewi Sri; Hendriyana, Hendriyana; Purkon, Haikal Muhammad; Nadila, Ai Salsa; Nugraha, Mochammad Suva (Jurnal PkM MIFTEK, 2023)
MSMEs are required to be able to compete and create products that can be accepted, not only by domestic consumers (Indonesia) but also consumers in Southeast Asia. MSMEs are able to support large businesses, such as providing raw materials, spare parts and other supporting materials. Therefore, through this Real Work Lecture (KKN) program, Group 10 KKN conducts training and assistance to Micro, Small and Medium Enterprises actors in Wanaraja Village for 1 month. With the aim of helping and providing an understanding of how very influential branding and packaging design are in product marketing in the market. As for the results achieved by Micro, Small and Medium Enterprises, their products will have product branding and logos and be able to market MSME products online.